Intermittent and Persistent Type 2 lupus: patient perspectives on two distinct patterns of Type 2 SLE symptoms. Issue 1 (5th August 2022) - Eudy, Amanda M; Rogers, Jennifer L; Corneli, Amy; McKenna, Kevin; Maheswaranathan, Mithu; Pisetsky, David S; Criscione-Schreiber, Lisa G; Doss, Jayanth; Sadun, Rebecca E; Sun, Kai; Clowse, Megan E B
Abstract : Objective: We have developed a new conceptual model to characterise the signs and symptoms of SLE: the Type 1 and 2 SLE Model. Within the original model, Type 1 SLE consists of inflammatory manifestations like arthritis, nephritis and rashes; Type 2 SLE includes symptoms of fatigue, myalgia, mood disturbance and cognitive dysfunction. Through in-depth interviews, we explored how the Type 1 and 2 SLE Model fits within the lived experience of patients with SLE, with a focus on the connection between Type 1 and Type 2 SLE symptoms. Methods: Semistructured in-depth interviews were conducted among adult participants meeting 1997 American College of Rheumatology or Systemic Lupus International Collaborating Clinics criteria for SLE. Participants were purposefully selected for age, race, sex and nephritis history. All interviews were audio-recorded and transcribed. Data were analysed through episode profile and thematic analysis. Results: Through interviews with 42 patients with SLE, two patterns of Type 2 SLE emerged: Intermittent (n=18) and Persistent (n=24). Participants with Intermittent Type 2 SLE described feeling generally well when Type 1 is inactive; these participants were younger and had more internal SLE manifestations. Participants with Persistent Type 2 described always experiencing Type 2 symptoms despite inactive Type 1, although the severity may fluctuate. Participants with Persistent Type 2 SLE experienced traditional lupus symptoms of joint pain, hair loss and rash, but less often had severe organ system involvement. Conclusions: By listening to the stories of our patients, we found two underlying patterns of Type 2 SLE: Intermittent Type 2 symptoms that resolve in synchrony with Type 1 inflammatory symptoms, and Persistent Type 2 symptoms that continue despite remission of Type 1 symptoms.